Advantages of fluid and white matter suppression (FLAWS) with MP2RAGE compared with double inversion recovery turbo spin echo (DIR-TSE) at 7T. Issue 116 (July 2019) - Urushibata, Yuta; Kuribayashi, Hideto; Fujimoto, Koji; Kober, Tobias; Grinstead, John W; Isa, Tadashi; Okada, Tomohisa
Highlights: A 7T-MRI is a cutting-edge non-invasive human imaging system. CSF and WM signal suppression increases contrast to detect brain lesions. Two suppression methods, FLAWS-MP2RAGE and DIR-TSE, were compared at 7T. FLAWS-MP2RAGE showed lower SAR and more homogenous GM delineation. Adoption of FLAWS-MP2RAGE at 7T is expected to facilitate lesion detection. Abstract: Cerebrospinal fluid (CSF) and white matter (WM) signal suppression techniques allow better visualization of both WM and gray matter (GM) lesions in such disorders as multiple sclerosis and epilepsy. Recently, a technique, FLuid And White matter Suppression "FLAWS", has been proposed at 3 T based on the magnetization-prepared with two rapid gradient echoes (MP2RAGE) sequence. In this study, the FLAWS-MP2RAGE pulse sequence was compared with a double inversion recovery turbo spin echo (DIR-TSE) sequence at 7 T. Twenty-two healthy volunteers were examined. Isotropic spatial resolution of 1 mm and a scan time of approximately 6 min were chosen due to a restricted clinical schedule. Homogeneity of CSF and WMs ignal suppression was compared with GM signal as an intensity reference. Volumes of GM visualization and specific absorption rates (SARs) were compared using Wilcoxon-rank sum tests with Bonferroni-Holm correction for multiple comparisons. WM-to-GM signal ratios in FLAWS-MP2RAGE images were significantly lower than DIR-TSE (median: 24.5% vs 59.0%, P  <  0.0001), whereas CSF-to-GM signal ratios in FLAWS-MP2RAGE were significantly higher than DIR-TSE (57.1% vs 38.3%, P  =  0.0001). Ranges of the signal ratios between 20 and 80 percentiles were lower in FLAWS-MP2RAGE than DIR-TSE for WM (24.1% vs 37.2%, P  <  0.0001) but were higher in FLAWS-MP2RAGE compared with DIR-TSE for CSF (80.8% vs 63.0%, P  =  0.0001). Pixels of low GM signal (< 20% of the median) were mainly distributed at the skull base, and these low signal GM volume ratios were lower in FLAWS-MP2RAGE than DIR-TSE (2.27% vs 6.18%, P  <  0.0001). Median SAR in sixteen subjects was 2.5 times higher in DIR-TSE than in FLAWS-MP2RAGE. FLAWS-MP2RAGE showed superior and more homogenous WM signal suppression, better GM visualization at the skull base and lower SAR compared with DIR-TSE, suggesting superiority of FLAWS-MP2RAGE at 7 T.